2015
DOI: 10.1055/s-0035-1551682
|View full text |Cite
|
Sign up to set email alerts
|

High-Risk Cardiac Surgery in Patients with Intravenous Drug Abuse and/or Active Hepatitis C or HIV Infection: An Ethical Discussion of Six Cases

Abstract: Decision making in noncompliant drug addicts with recurrent prosthesis infection and in HIV-positive patients leads beyond surgical challenges to ethical and economic considerations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 0 publications
0
15
0
Order By: Relevance
“…[6,7] Hepatitis C co-infection poses numerous problems; in addition to long-term risks such as liver cirrhosis and cancer, and transmission of infection to others, it also presents ethical dilemmas with regard to surgery in IDUs. [8,9] In addition, significant costs are associated with the treatment of hepatitis C infection, often in non-compliant patients, who frequently have other concurrent opportunistic infections associated with HIV. [10] In agreement with previous literature on IE in IDUs, the majority of the patients in this study were HIV-positive.…”
Section: Discussionmentioning
confidence: 99%
“…[6,7] Hepatitis C co-infection poses numerous problems; in addition to long-term risks such as liver cirrhosis and cancer, and transmission of infection to others, it also presents ethical dilemmas with regard to surgery in IDUs. [8,9] In addition, significant costs are associated with the treatment of hepatitis C infection, often in non-compliant patients, who frequently have other concurrent opportunistic infections associated with HIV. [10] In agreement with previous literature on IE in IDUs, the majority of the patients in this study were HIV-positive.…”
Section: Discussionmentioning
confidence: 99%
“…An important recent study of surgical outcomes for isolated IVDU-associated tricuspid valve infective endocarditis, utilizing The Society of Thoracic Surgeons (STS) adult cardiac surgery database, and using a contemporary cohort of patients demonstrates that valvectomy was an independent predictor of operative mortality (14). Prior reports have demonstrated that long-term survival without a tricuspid valve is feasible (up to 22 years) in the context of normal pulmonary artery pressures and/ or pulmonary vascular resistance (11,15). The lack of significant differences in perioperative outcomes, coupled with high prosthetic valve infection and readmission rates seen in patients treated with valve replacement at their initial operation, helps to establish tricuspid valvectomy as a useful bridge to staged valve replacement in this highrisk patient population.…”
Section: Random Effects Modelmentioning
confidence: 99%
“…The decision of choice and whether to offer surgical therapy for patients with IVDU-associated infective tricuspid valve endocarditis is a complex one-with social considerations (willingness to abstain from IVDU, compliance with antibiotic therapy stable income, stable housing, detoxification and rehabilitation), clinical considerations (size of vegetations, extension of abscess, comorbid HIV and hepatitis C infection) and ethical considerations (prolong life expectancy, risk of recurrence, healthcare expenditures and resource allocation) (15). IVDU is an independent predictor of death in patients with endocarditis and should be considered strongly in surgical recommendations for this complicated population (1,13,17).…”
Section: Random Effects Modelmentioning
confidence: 99%
“…One of the most painful issues reported by our participants was surgery for patients with HIV, which they were refused by hospitals, by specialists and medical staff. Gansera et al (2016) in a study in Germany, reported that there is support for not performing cardiac surgery in patients with hepatitis C and HIV infection and a number of patients reported that some hospitals refused to admit them (13). A qualitative study by Gwala-Ngozo et al in 2010 held individual interviews with 15 physicians about performing surgery and found four areas of concern in the experiences of surgeons regarding performing surgery on patients with HIV/AIDS: personal factors, patient factors, factors related to the structure of the health system, and factors related to the treatment protocol of patients with HIV/AIDS.…”
Section: Discussionmentioning
confidence: 99%